Coronary Microvascular Dysfunction in Acute Cholestasis-Induced Liver Injury - Sebastian Billig; Marc Hein; Celine Kirchner; David Schumacher; Moriz Aljoscha Habigt; Mare Mechelinck; Dieter Fuchs; Uwe Klinge; Alexander Theißen; Christian Beckers; Christian Bleilevens; Rafael Kramann; et al. (Biomedicines, 2024)
Background: Previous studies have shown cardiac abnormalities in acute liver injury, suggesting a potential role in the associated high mortality. Methods: We designed an experimental study exploring the short-term effects of acute cholestasis-induced liver injury on cardiac function and structure in a rodent bile duct ligation (BDL) model to elucidate the potential interplay. Thirty-seven male Sprague-Dawley rats were subjected to BDL surgery (n = 28) or served as sham-operated (n = 9) controls. Transthoracic echocardiography, Doppler evaluation of the left anterior descending coronary artery, and myocardial contrast echocardiography were performed at rest and during adenosine and dobutamine stress 5 days after BDL. Immunohistochemical staining of myocardial tissue samples for hypoxia and inflammation as well as serum analysis were performed. Results: BDL animals exhibited acute liver injury with elevated transaminases, bilirubin, and total circulating bile acids (TBA) 5 days after BDL (TBA control: 0.81 ± 2.54 µmol/L vs. BDL: 127.52 ± 57.03 µmol/L; p < 0.001). Concurrently, cardiac function was significantly impaired, characterized by reduced cardiac output (CO) and global longitudinal strain (GLS) in the echocardiography at rest and under pharmacological stress (CO rest control: 120.6 ± 24.3 mL/min vs. BDL 102.5 ± 16.6 mL/min, p = 0.041; GLS rest control: −24.05 ± 3.8% vs. BDL: −18.5 ± 5.1%, p = 0.01). Myocardial perfusion analysis revealed a reduced myocardial blood flow at rest and a decreased coronary flow velocity reserve (CFVR) under dobutamine stress in the BDL animals (CFVR control: 2.1 ± 0.6 vs. BDL: 1.7 ± 0.5 p = 0.047). Immunofluorescence staining indicated myocardial hypoxia and increased neutrophil infiltration. Conclusions: In summary, acute cholestasis-induced liver injury can lead to impaired cardiac function mediated by coronary microvascular dysfunction, suggesting that major adverse cardiac events may contribute to the mortality of acute liver failure. This may be due to endothelial dysfunction and direct bile acid signaling.